IMPROVING STUDENTS’ WRITING SKILL OF DESCRIPTIVE PARAGRAPH THROUGH MIND MAPPING METHOD - DWI SUCI AMANIARSIH; NURMAHYUNI ASRUL; Meida Rabia Sihite (Universitas Suryakancana, 2020)
The purpose of this study is to find out how the application of mind mapping method in improving students’wrting skill of descriptive paragraph of grade X students in SMA Harapan 3 Medan Harapan 3 Medan. This research is a Classroom Action Research. The subjects in this study were students of grade X SMA harapan 3 Medan.. While the object of this study is the application of mind mapping method in improving students’ writing skill of descriptive paragraph . Based on the results of the study, it was found that from the results of the action as much as 2 (two) cycles in grade X students of SMA Harapan 3 Medan concluded that the use of mind mapping method can improve writing skill of descriptive paragraph. From the results of the Cycle I and Cycle II activities as many as 70% of students were declared complete in the writing material of descriptive text with an average value of 71. Thus this study was stated to be successful and it could be said that the use of mind mapping method could improve students'wrting skill of descriptive paragraph.